Micro-CT Study of Mongolian Gerbil Humeral Bone After Prolonged Spaceflight Based on a New Algorithm for Delimitation of Long-Bone Regions - Krivonosov, Yuri S.; Gulimova, Victoria I.; Buzmakov, Alexey V.; Zolotov, Denis A.; Cedola, Alessia; Bukreeva, Inna; Asadchikov, Victor E.; Saveliev, Sergey V. (Frontiers in Physiology, 2021)
The Mongolian gerbil display unique physiological and anatomical features that make this species an attractive object for biological experiments in space. However, until recently, Mongolian gerbil has remained a novel, mostly unstudied animal model in investigating bone loss in weightlessness (G0). After 12 days of orbital Foton-M3 mission, the humerus of Mongolian gerbils has been studied here via micro-computed tomography to quantify bone morphometric parameters. The samples from the flight group, delayed synchronous ground-control group and basal control group were investigated, and main morphometric parameters were reported in the article. The accurate selection of a region of interest is an essential step for a correct assessment of bone parameters. We proposed a new, easy and efficient method for delimiting the bone’s basic regions in the humerus. It is based on quantitative estimation of X-ray attenuation in cortical bone as a function of humerus bone length. The micro-CT analysis of the basic bone regions revealed a difference in bone morphometric parameters between the flight and control gerbils. The most significant bone loss was observed in the cortical part of the proximal humeral zone in the flight group. No statistically significant changes of volume fraction in the cancellous tissue of proximal and distal epiphyses and metaphyses were observed. A statistically significant increase in both cancellous bone volume and bone X-ray attenuation in the flight group was detected in the proximal part of diaphyses. We assume that enhanced calcium deposition in the diaphyseal cancellous tissue occurred due to a bone response to G0 conditions.